Analýza systému řízení lidských zdrojů ve vybraném podniku - Husinecká, Lenka (Jihočeská univerzita, 2011)
Svou diplomovou práci jsem zpracovala na dvě části. V první části jsem se zabývala základními pojmy jako motivace, ovlivňováním, adaptace, vedení, řízení lidských zdrojů, hodnocení. V druhé části diplové práce je popsána situace společnosti BRVZ s.r.o. Jako prostředek jsem zvolila zaměstnanecký dotazník.
Analysis of the human resources in the selected company
Keywords: My diploma thesis was elaborated in two parts. The first part dealt with basic concepts such as motivation; interaction; adaptation; management; human resources; evaluation. In the second part diplom thesis is escribed a situation of the company BRVZ s.r.o. As a means I chose an employee questionnaire.; motivation; stimulation; remuneration; satisfaction of the staff; control.